The Relationship Between Science Process Skills and Concept Mastery Using Practical Methods - Aulia Novitasari; Sintasari, Rantrika; Kesumawardani, Aryani Dwi; Supriyadi, Supriyadi (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Science process skills and conceptual mastery are two crucial aspects. Conceptual mastery involves understanding scientific concepts, while science process skills encompass the ability to conduct scientific work, apply concepts, predict and inquire, interpret and communicate, hypothesize, conclude, plan, and conduct experiments. The aim of this study is to determine the relationship between science process skills and conceptual mastery through practical methods. The research method employed is quantitative with a correlational design. The study population includes all 11th-grade MIPA students at SMA Negeri 1 Bumi Agung, Lampung, with cluster random sampling used to select Class XI MIPA 1 as the sample. Data collection involved observation sheets and tests. Data analysis was conducted using Pearson product-moment correlation coefficient. The correlation analysis began with testing prerequisites such as normality and linearity, confirming that the data were normally distributed and linear. The correlation between science process skills and conceptual mastery yielded an pearson correlation coefficient (r) of 0.940 with N = 32. The critical value (r-table) was 0.349. Since 0.940 > 0.349 and the significance value (2-tailed) was 0.00 < 0.05, H0 was rejected and H1 was accepted, indicating a very strong relationship between science process skills and conceptual mastery through practical methods. Theoretically, these findings affirm the importance of practice-based learning in strengthening conceptual understanding. Practically, the results recommend integrating structured laboratory activities to enhance students’ scientific inquiry skills and conceptual mastery.